2012
DOI: 10.1038/labinvest.2012.111
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-like protein 2 mediates endotoxin-induced acute inflammation in the eye

Abstract: Angiopoietin-like protein (Angptl) 2 is a key mediator linking obesity to chronic adipose-tissue inflammation and systemic insulin resistance, and increasing evidence has shown that Angptl2 is associated with various chronic inflammatory diseases such as cancer and dermatomyositis; however, it remains unclear that Angptl2 functions in acute inflammation. In this study, we investigate whether Angptl2 has a role in acute inflammation in the eye with endotoxin-induced uveitis (EIU). Angptl2 was widely expressed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 37 publications
3
33
0
Order By: Relevance
“…Consistent with previous mouse EIU studies, the number of leukocytes that firmly adhered to the retinal vasculature in WT or vehicle-treated eyes was significantly increased during EIU [4,5]. Importantly, our study established, using genetic and pharmacological approaches, that MMP-3 is involved in leukocyte adhesion during acute inflammation in the eye.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with previous mouse EIU studies, the number of leukocytes that firmly adhered to the retinal vasculature in WT or vehicle-treated eyes was significantly increased during EIU [4,5]. Importantly, our study established, using genetic and pharmacological approaches, that MMP-3 is involved in leukocyte adhesion during acute inflammation in the eye.…”
Section: Discussionsupporting
confidence: 91%
“…These studies are of fundamental significance to increase our understanding of ocular inflammation, as inflammatory processes and BRB dysfunctions are strongly implicated in the pathogenesis of highly prevalent ocular diseases such as diabetic retinopathy, age-related macular degeneration (AMD), Behçet’s disease, retinitis pigmentosa and posterior uveitis [4,49,50]. Therefore, a potential common therapeutic strategy in combatting these disorders will presumably link with the regulation of inflammatory processes [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous report indicated that ANGPTL2 derived from retinal cells or macrophages leads to leukocyte adhesion, infiltration, and expression of pro-inflammatory cytokines such as TNF-α in the acute phase of endotoxin-induced uveitis. [8] Here, we provide additional evidence that ANGPTL2 functions in acute cerebral ischemia and worsens neurological deficits, increases infarct volume, and promotes expression of neurotoxic inflammatory cytokines, including TNF-α and IL-1β (Fig 6). …”
Section: Discussionmentioning
confidence: 63%
“…[5] However, once the vascular network known as the blood brain barrier (BBB) is disrupted by ischemia, circulating or perivascular macrophages infiltrate the parenchyma of brain tissue. [3] Activated infiltrated macrophages cause neuronal injury by amplifying inflammation via secretion of pro-inflammatory cytokines such as interleukin (IL)-1β[6, 7] or tumor necrosis factor (TNF)-α[8]. Sustained inflammation in ischemic brain caused by pro-inflammatory cytokines further injures neurons.…”
Section: Introductionmentioning
confidence: 99%